Safety and immunogenicity of inactivated hepatitis-A vaccine developed by Human Biologicals Institute in two age groups of healthy subjects: A phase I open label study. Issue 15 (8th April 2021) - Susarla, Sai Krishna; Palkar, Sonali; SV, Pardha Saradhi; Diwan, Arundhati; Barsode, Supriya; Satish, M.; Rajashakar, BC; Sandhya, G.; Lingala, Rajendra; Sahoo, Devi Prasad
Abstract: Background: Hepatitis-A is an acute viral infection of the liver. Hepatitis-A virus has worldwide spread and is endemic in India. Though the disease is self-limiting in most cases, outbreaks are reported frequently from both developing and developed countries of the world. Severity and fatality occur more among infected symptomatic adults. The infection can be prevented with proper and timely immunization. This phase I, single arm, open label, multicenter trial was designed to assess the safety and immunogenicity of the inactivated hepatitis-A vaccine developed by Human Biologicals Institute when administered in a single dose in two age groups of healthy subjects. Methods: This study was carried out in 55 subjects in two healthy age groups at two centers in India. Group A included subjects of 19–49 years and group B subjects of 12–18 years of age. Enrolled subjects received a single dose of inactivated hepatitis A vaccine. Blood samples were collected at baseline and 4–6 weeks after vaccination. Safety was assessed by collection and analysis of data on solicited and unsolicited adverse events and immunogenicity was assessed by estimating the seroconversion rate, seroprotection rate and the geometric mean titres of antibodies. Results: Among the 55 subjects enrolled, 15 reported adverse events. No serious adverse event was reported. Pain at the injection site was the lone local adverse event. Systemic adverse events reported in Group A were: fatigue, headache, diarrhoea, fever, anorexia, nausea and upper respiratory tract infection, whereas there was no systemic event reported in Group B. There was 100% seroconversion and seroprotection and significant rise in antibody titre levels were observed in both the groups post vaccination. Conclusions: This study found HBI inactivated hepatitis-A vaccine to be safe and highly immunogenic when administered as a single dose in adolescent and adult subjects.